Implementasi Sistem Penilaian Kurikulum 2013 pada Mata Pelajaran Matematika - Ahmad, Nurul Qomariyah; Harahap, Rosliana; Amalia, Anisa (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2023)
The assessment system needs to be adjusted to the development and needs to control the quality of education. This study aims to determine the implementation of the curriculum assessment system in class VII mathematics subjects in MTsN 1 Takengon and its constraints. Using descriptive qualitative methods with interview guideline instruments, observation, documentation. The validity of the data by engineering triangulation and data analysis based on Miles and Huberman's theory. Based on the results of research, teachers have applied the principles of assessment, an assessment mechanism that includes making minimum completion criteria (KKM), the existence of an assessment plan written in the learning implementation plan. In addition, teachers conduct an assessment of attitudes, knowledge, skills in the form of assessment including daily assessment, self-assessment, test, midterm assessment (PTS), final assessment (PAS) which is finally processed into report card scores. Meanwhile, the obstacles faced by teachers need to learn to convert grades in processing report cards.